Valorization of the waste heat from a sulfuric unit for the refrigerated storage of ammonia - Elghaeb, Yasmine; Aicha, MABROUK; Jalel, BELGHAIEB; Nejib, HAJJI (IJRDO-Journal of Applied Science, 2021)
In the Tunisian Chemical Group, the production of sulfuric acid by the contact process yields important waste heat that measure about 22 MW of 1500 tons /day. This heat is discharged into the sea which, in addition to the resulting losses, constitutes a nuisance to the environment. To overcome this problem, it was proposed to recover part of this waste and use it for an absorption refrigeration machine. Now, ammonia is stored at atmospheric pressure and a temperature of -33 ° C. So that it remains in the liquid state, significant amounts of heat must be eliminated continuously. A compression refrigeration cycle is designed for it, but consumes a huge amounts of electricity. Unlike absorption heat pumps, which consume thermal discharges of the sulfuric unit. This paper presents a technical feasibility study for the use of waste heat generated by the sulfuric unit for the refrigerated storage of ammonia. It is proposed as a solution to conduct a heat recovery loop with ejector for the production of steam from this heat waste. This steam is then used for an absorption machine to keep ammonia at the liquid state. The simulation of the loop was done by Hysys and for the absorption refrigeration machine, the calculations were done by using EES as well as Oldham and Merkel diagrams. The obtained results indicated that the generator temperature must be higher than 134 °C for the absorption machine to operate when ammonia-water is the working pair. Moreover, a COP of about 0.46 was obtained for a generator temperature of 145°C and a condensation and absorption temperature of 37°C. This COP is very satisfactory for a single effect water-ammonia refrigeration cycle which is cooling to such a low temperature.